THE EFFECT OF DISCLOSURE ENTERPRISE RISK MANAGEMENT, INTELLECTUAL CAPITAL, AND SUSTAINABILITY REPORT ON COMPANY VALUE (A STUDY ON MINING SECTOR COMPANIES LISTED ON THE INDONESIA STOCK EXCHANGE IN THE PERIOD 2017 - 2021) - Leny Suzan; Andi Muhammad Rayhan (UNIVERSITAS PAKUAN, 2024)
The company value reflects the execution of the company as reflected within the request and supply of the capital advertise. This esteem speaks to society's appraisal of the quality of the company's execution. When the company esteem increments, its stock cost also tends to rise, which suggests shareholders pick up benefit. This investigate points to recognize the impact of endeavor hazard administration, mental capital, and maintainability report revelation on the company esteem within the mining division amid the period of 2017-2021. The free factors in this consider incorporate endeavor chance administration, mental capital, and maintainability report, whereas the subordinate variable is the company esteem. This ponder employments a quantitative strategy with purposive testing strategy. A add up to of 10 companies were chosen as inquire about tests for a five-year period, coming about in a add up to of 50 perception information tests. The investigation was conducted utilizing board information relapse strategy with the help of Eviews 12 computer program. Based on the conducted tests, the comes about appear that at the same time, undertaking hazard administration, mental capital, and sustainability report have an affect on the company esteem. Independently, mental capital contains a critical impact on the company esteem, whereas venture hazard administration and maintainability report don't have a noteworthy impact. This investigate is anticipated to encourage companies to progress inside viewpoints in arrange to upgrade the company esteem. Future analysts are empowered to include other potential autonomous factors which will influence the company value.